Peningkatan Pengetahuan Ibu dalam Pengolahan Tanaman Obat Keluarga (TOGA) sebagai Relaksan dan Skrining Kesehatan Jiwa - Widea Rossi Desvita; Tri Ani Marwati; Fikri Achmad Arif; Isabella Meliawati Sikumbang; Laela Hayu Nurani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The COVID-19 pandemic impacts maternal psychological problems with an increasing prevalence of symptoms of depression and anxiety. In Branch Aisyiyah Demangan and Sapen DIY, activities were stopped during the pandemic, considering that many of the members were elderly and were in the red zone in June 2021. On this basis, it is necessary to carry out stimulus activities that can be carried out during a pandemic. This activity aims to know mental health conditions by screening mental health, promoting mental health, and using and managing traditional medicines for relaxants. The methods used in this activity are mental health screening, mental health counseling and training, presentation of herbal medicines with the right dose, and making herbal medicine that meets the standards of the Health Office. Activities are carried out online, starting with pretest, delivery of material, mental health screening, management of traditional medicinal plants, post-test. The analysis of the results was carried out by performing a paired t-test statistical test. The pretest and post-test results showed an increase from 82±0.55 to 93±0.84. Psychologically and emotionally, most respondents experienced complaints of fatigue (73.1%), followed by complaints of difficulty understanding feelings (46.2%), then complaints of anxiety, tension, or worry (42.3%). Screening results show that one respondent has a mild mental problem.